Empirical Guidelines for Comparing International Accounting data - Nair, R. D. (Journal of International Business Studies, 1982)
This paper develops guidelines for comparing financial accounting data from different countries. Groups of countries that have similar accounting practices are identified as a basis for making valid comparisons. The distinction between measurement and disclosure practices is recognized and separate groupings are identified for each of these 2 subsets of accounting practices. The data come from the Price Waterhouse & Co. survey of 267 accounting practices in 64 countries in 1979. This study confirms the findings of earlier studies that the groupings on the basis of disclosure practices exhibit greater diversity and are less stable over time than such groupings on the basis of measurement practices.